2014
DOI: 10.1523/jneurosci.1414-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

LTP and LTD in the Visual Cortex Require the Activation of NOX2

Abstract: Reactive oxygen species (ROS) are signaling factors involved in many intracellular transduction pathways. In the nervous system, ROS are thought to modulate various mechanisms of synaptic plasticity. One important source of ROS production in the brain is the NADPH oxidase complex. Stimulation of NMDA receptors activates NADPH oxidase, which provides selective oxidative responses accompanying the induction of synaptic changes. The activity of NADPH oxidase is known to be crucial for the induction of LTP in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
3
24
1
Order By: Relevance
“…Considering ROS as highly reactive and diffusible molecules, NOX2 activation could be involved in the metaplastic regulation of synaptic changes. In agreement with this idea, previous studies demonstrated that nonfunctional NOX2 impairs synaptic plasticity in the hippocampus and visual cortex (Kishida et al, 2006;De Pasquale et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
See 4 more Smart Citations
“…Considering ROS as highly reactive and diffusible molecules, NOX2 activation could be involved in the metaplastic regulation of synaptic changes. In agreement with this idea, previous studies demonstrated that nonfunctional NOX2 impairs synaptic plasticity in the hippocampus and visual cortex (Kishida et al, 2006;De Pasquale et al, 2014).…”
Section: Introductionsupporting
confidence: 69%
“…In a previous work, it was shown that synaptic plasticity is impaired in gp91 phoxϪ/Ϫ mice and that this is due to a deficiency in NMDAR functioning (De Pasquale et al, 2014). However, here, we demonstrated that plasticity "reopens" in the direction of LTD when gp91 phoxϪ/Ϫ animals are reared in the dark.…”
Section: Nox2 and Dark Rearing Modulate The Activity Of Nmdarscontrasting
confidence: 50%
See 3 more Smart Citations